Fictions of Feminine Citizenship - Francis, D. author. aut Link
VIII, 191 p.
Keywords: Reading novels by contemporary women in the Caribbean dyaspora alongside and against law, history and anthropology, the book argues that Caribbean women's sexuality has been mobilized for various imperialist and nationalist projects from the nineteenth century to present.